A LINK BETWEEN STUDENTS' MOTIVATION TO LEARN ENGLISH AND TEACHERS' TEACHING PHILOSOPHIES - Bachtiar, Aulia Mutmainna; Jabu, Baso; Aeni, Nur (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
The study aims to find out the correlation between the teaching style of the teacher and the motivation of the student in learning English. The type of research used in this study is quantitative research with the subject of research students of class X SMAN 1 Kalukku Teaching Year 2023/2024 where there are 105 students in which there are three classes that are samples in this research namely class X.1, X,2, and X.3. This research variable consists of a bound variable and a free variable. The bound Variable of this research is the correlation between the teaching style of the teacher and the motivation of the student in the learning of the English language while for the variable free of this study is the teacher's learning style. The instrument used in this research is a questionnaire that contains information about the teaching style of the teacher and the motivation of the student to learn. The analysis of the research data uses descriptive statistical analysis in the form of percentages and correlation analysis with the Spearman Correlation Test. The results of the study showed that there was a strong correlation between the Teaching Style and Student Motivation in SMAN 1 Kaluku with a correlative value of 0.588 which means that the presence of some teaching style indicators increased student motivation and the determination coefficient of 34.5% which means the variation of the teacher's teaching styling model was 34.5% and the rest was determined by other factors. Of the five types of teaching styles given Facilitator style which had a strong Correlation with Student Motivations SMAN1 Kaluku was 0.604 and a determination factor of 36.48%. So based on the findings and data analysis available it can be concluded that the teacher's learning style has a strong influence on student learning motivation in learning English.